(untitled) (Unilorin Journal of Lifelong Education, 2025)
Early childhood care, development and education (ECCDE) plays a vital role in shaping children’s cognitive, emotional, and social development. In Nigeria, the Universal Basic Education (UBE) programme seeks to provide quality and accessible education for children from early childhood through Junior Secondary School (JSS 3). A key component of the UBE programme is the establishment of linkage schools, which are designed to serve as models of quality early education. These schools are meant to bridge the gap between formal and informal early childhood education, creating an integrated system that improves access to early learning opportunities, particularly in underserved regions. However, despite the potential of ECCDE linkage schools, various challenges such as inadequate infrastructure, insufficient teacher training, low community participation, and limited funding hinder their ability to deliver quality education. This paper critically examines the current state of ECCDE linkage schools in Nigeria and identifies key obstacles that prevent them from meeting their educational objectives. The paper offers a set of actionable strategies aimed at strengthening these schools to improve early childhood development outcomes across the country. The proposed strategies include policy reforms, increased funding, enhanced teacher training, improved infrastructure, and stronger community involvement. Ultimately, the paper argues that addressing these challenges and implementing the recommended interventions is essential for fostering a sustainable, high-quality early education system in Nigeria.